The power of the pen reconsidered: The media, CEO human capital, and corporate governance - Liu, Baixiao; McConnell, John J.; Xu, Wei (Journal of Banking & Finance, 2017)
By examining the post-retirement outside board seats held by former CEOs of S&P 1500 firms, we find that CEOs’ post-retirement outside board memberships are influenced by the level and the tone of media coverage given to the CEOs’ firms while the CEOs were “on the job.” These results provide evidence of a direct economic link between media coverage of CEOs’ performance today and CEOs’ future opportunity sets. These results lend support to the proposition that the media can play a role in corporate governance by influencing the value of CEOs’ human capital.